Two-Dimensional Rubble-Mound Breakwater Model Using Tetrapod at Armor Layer and Geotube at Core Layer - Pattipawaej, Olga; Dani, Hanny; Samskerta, I. Putu (Universitas Muhammadiyah Surakarta, 2015)
Waves and currents can remove sand from the coastal areas that caused beach erosion. Beach erosion needs to be handled by building breakwater. Rubble mound breakwater is chosen to dissipate the wave energy. Rubble mound structures are widely used throughout the world; so naturally, stability tests of rubble mound structures are the most frequently conducted coastal structure model. Two-dimensional rubble mound structure physical model is carried out in a flume. The armor layer facing the seaward uses tetrapods that are placed randomly and the core layer is set to be stable by using geotube. Three different slopes of rubble mound model facing the seaward is applied, i.e., 1:1.5, 1:2, and 1:2.5, respectively. There are also four different water levels used, i.e., 38 cm, 54 cm, 63 cm, and 70 cm. The measured parameters of this study are the wave height and wave period in front of and behind the breakwater structure. The analysis that can be done is the wave absorber and transmission waves. The stability of the structure can be observed in the form of displacement armor testing on the breakwater and at toe for a wide variety of slope and water level variations.